Colonial Echoes in Digital Spaces: A Critical Discourse Analysis of English Teaching on Instagram - Af’idatul Husniyah; Titien Indrianti (Transpublika Publisher, 2025)
The global spread of English has long been entangled with colonialism, imperialism, and unequal power relations. Although English is now spoken predominantly by multilingual users outside traditionally Anglophone nations, dominant norms continue to privilege so-called “native” speakers from the Global North. This study critically analyzes how English Language Teaching (ELT) materials on Instagram reproduce or resist colonial ideologies through digital discourse. Drawing on Critical Discourse Analysis (CDA) and a decolonial framework, the research examines the linguistic, visual, and ideological dimensions of ELT content produced by teachers, influencers, and language schools on Instagram. The analysis focuses on how English is represented, commodified, and associated with modernity, prestige, success, and global citizenship. Using Fairclough’s three-dimensional model (text, discursive practice, and social practice) and Kress and van Leeuwen’s multimodal discourse analysis, the study examines how colonial discourses position “native” English as the norm and Global South learners as aspirational subjects requiring linguistic correction despite Anglophone users no longer constituting the majority of English speakers. The study reveals Instagram as a site of digital colonialism where English operates as both symbolic capital and cultural commodity. Findings identified clear colonial echoes in ELT content, including the use of “bule” as a benchmark, the promotion of white accents and accent hierarchy, and the Westernization of “global.” These practices reinforce racial and cultural hierarchies by positioning Western identities, languages, and aesthetics as the standard for English proficiency and global modernity.